The social benefits of urban open green spaces: a literature review - Rakhshandehroo, Mehdi; Mohd Yusof, Mohd Johari; Mohd Tahirholder, Osman; Mohd Yunos, Mohd Yazid (Bucharest University of Economic Studies, 2015)
In the process of rapid urbanization and domination of concrete overnature, lifestyles have changed. Since natural landscape and greenery are crucially important to our quality of life and the majority of the population are going to settle down in urban areas, urban open green spaces as the ‘lungs of the city’ are often at the center of the debate on urban planning and sustainable development. The overall aim of this paper is to investigate the social, health, environmental and economic benefits of providing urban open green space. The many benefits of urban open green spaces were investigated in a systematic review of scientific online databases, relevant research and other related papers.